L-cysteine administration attenuates pancreatic fibrosis induced by TNBS in rats by inhibiting the activation of pancreatic stellate cell. - LiJuan Yang (Public Library of Science (PLoS), 2012)
Background and aims Recent studies have shown that activated pancreatic stellate cells (PSCs) play a major role in pancreatic fibrogenesis. We aimed to study the effect of L-cysteine administration on fibrosis in chronic pancreatitis (CP) induced by trinitrobenzene sulfonic acid (TNBS) in rats and on the function of cultured PSCs. Methods CP was induced by TNBS infusion into rat pancreatic ducts. L-cysteine was administrated for the duration of the experiment. Histological analysis and the contents of hydroxyproline were used to evaluate pancreatic damage and fibrosis. Immunohistochemical analysis of α-SMA in the pancreas was performed to detect the activation of PSCs in vivo. The collagen deposition related proteins and cytokines were determined by western blot analysis. DNA synthesis of cultured PSCs was evaluated by BrdU incorporation. We also evaluated the effect of L-cysteine on the cell cycle and cell activation by flow cytometry and immunocytochemistry. The expression of PDGFRβ, TGFβRII, collagen 1α1 and α-SMA of PSCs treated with different concentrations of L-cysteine was determined by western blot. Parameters of oxidant stress were evaluated in vitro and in vivo. Nrf2, NQO1, HO-1, IL-1β expression were evaluated in pancreas tissues by qRT-PCR. Results The inhibition of pancreatic fibrosis by L-cysteine was confirmed by histological observation and hydroxyproline assay. α-SMA, TIMP1, IL-1β and TGF-β1 production decreased compared with the untreated group along with an increase in MMP2 production. L-cysteine suppressed the proliferation and extracellular matrix production of PSCs through down-regulating of PDGFRβ and TGFβRII. Concentrations of MDA+4-HNE were decreased by L-cysteine administration along with an increase in GSH levels both in tissues and cells. In addition, L-cysteine increased the mRNA expression of Nrf2, NQO1 and HO-1 and reduced the expression of IL-1β in L-cysteine treated group when compared with control group. Conclusion L-cysteine treatment attenuated pancreatic fibrosis in chronic pancreatitis in rats.